Development Of An Interactive Compensatory Learning Model To Improve The Reading Comprehension Ability Of Grade Xi High School Students In Southeast Maluku Regency And Tual City, Maluku Province - M. Faqih Seknun; Usman Matdoan (Eduvest - Journal of Universal Studies, 2024)
Reading is one of the important competencies in English. So far there are still many high school students who cannot read English texts properly and correctly. Various efforts from the government to improve the quality of education in the field of English through updates to the curriculum, improvement of facilities and improvement of teacher quality. But this is still felt to be unanswered. This research aims to produce a reading learning model product that suits current and future needs in high school. This study used an approach Research and Development. The subjects of the study were 11 teachers and students in 10 schools in the research site. Data collection techniques were carried out using questionnaires, interviews, observations, documentation and tests. Data analysis techniques are carried out using qualitative and quantitative analysis techniques (statistical tests). The results showed that there were differences in students' English learning outcomes for the three groups of good, medium and less who used the learning model interactive Compensatory and conventional learning. This is shown statistically using the t test, where the group of both tcount values (22.58) > ttable (2.02); medium group t valuecount (17.19) > table (2.02); The group lacks tcount value (10.26) > ttable (2.02). Statistically it can be seen that learning using models Interactive Compensatory More effective in improving capabilities reading comprehesion rather than conventional learning. Reading techniques scanning, skimming, bottom-up, top-down In this study produced a reading model Interactive Compensatory.